Porosity of silica Stöber particles determined by spin-echo small angle neutron scattering. Issue 21 (29th March 2016) - Parnell, S. R.; Washington, A. L.; Parnell, A. J.; Walsh, A.; Dalgliesh, R. M.; Li, F.; Hamilton, W. A.; Prevost, S.; Fairclough, J. P. A.; Pynn, R.
Abstract : Open and closed volume fractions determined for Stöber silica in deuterated and hydrogenous solvents. Abstract : Stöber silica particles are used in a diverse range of applications. Despite their widespread industrial and scientific uses, information on the internal structure of the particles is non-trivial to obtain and is not often reported. In this work we have used spin-echo small angle neutron scattering (SESANS) in conjunction with ultra small angle X-ray scattering (USAXS) and pycnometry to study an aqueous dispersion of Stöber particles. Our results are in agreement with models which propose that Stöber particles have a porous core, with a significant fraction of the pores inaccessible to solvent. For samples prepared from the same master sample in a range of H2 O : D2 O ratio solutions we were able to model the SESANS results for the solution series assuming monodisperse, smooth surfaced spheres of radius 83 nm with an internal open pore volume fraction of 32% and a closed pore fraction of 10%. Our results are consistent with USAXS measurements. The protocol developed and discussed here shows that the SESANS technique is a powerful way to investigate particles much larger than those studied using conventional small angle scattering methods.